Sulh (Resolution) of Family Dispute and its Application in The Shariah Courts of Malaysia - Binti Che Adnan, Norfatin Najwa (Fakultas Syariah INSURI Ponorogo, 2024)
The resolution of family disputes through Sulh in Malaysia's Shariah courts represents a pivotal area of research that promotes peaceful conflict resolution, preserves familial bonds, and aligns with Islamic teachings and legal principles. This study examines the effectiveness of Sulh as an alternative dispute resolution (ADR) mechanism, emphasizing its capacity to address family conflicts in a culturally sensitive manner. By analyzing data from the Shariah Judiciary Department of Malaysia, which reported a considerable number of successfully resolved Sulh cases in 2021, the research underscores its role in expediting resolutions and alleviating case backlogs in Shariah courts. While Sulh demonstrates notable successes, public confidence in it remains limited compared to traditional litigation methods. The study seeks to identify factors contributing to the success of Sulh, proposing strategies to enhance its accessibility, transparency, and fairness. By offering actionable insights for policymakers, legal practitioners, and court administrators, this research aims to strengthen the Shariah court system's capacity to deliver justice efficiently, foster amicable agreements, and reduce the burden of extended litigation. Furthermore, the findings provide a foundation for legislative and legal reforms, including the development of comprehensive laws, guidelines, and training programs tailored to Sulh procedures. Ultimately, this research aspires to elevate public awareness and acceptance of Sulh as an effective ADR mechanism within the Islamic legal framework, promoting its broader adoption and understanding among Malaysians.